Absence of food aversion learning in the polyphagous noctuid, spodoptera litura (F.) following intoxication by deleterious chemicals - Ghumare, S. S.; Mukherjee, Samindra N. (Journal of Insect Behavior, 2005)
The objective of this study was to determine whether the presence of a deleterious chemical in a preferred host plant could alter the feeding preference of a polyphagous insect. The preference of the Asian armyworm, Spodoptera litura (F.) (Lepidoptera: Noctuidae) for castor, Ricinus communis (L.) (family: Euphorbiaceae) relative to cabbage, Brassica oleracea (L.) (family: Brassicaceae) was quantified by two separate two-way choice tests (without treatment and with treatment of the test chemicals used in the present study) with naive third instar larvae each time. This was followed, by continuous feeding (48 h) on the preferred host treated with the test chemicals and using naive third instar larvae for conditioning. Each treatment consisted of one of nine compounds, including seven naturally occurring allelochemicals (viz. (-)-alpha-pinene, (-)-beta-pinene, beta-myrcene, D-limonene, cineole, rutin, and ajwain oil) and two synthetic insecticides (viz. alphamethrin and malathion). Following this, a two-way choice test was repeated with the same batch of larvae without any test chemical. Larvae continued to maintain preference for castor despite exposure to the deleterious chemicals. Among the test chemicals, D-limonene and alphamethrin caused significant reduction in growth. Preference for castor was not overcome by exposure to novel deleterious chemicals, suggesting that aversion, though experienced is not learned.
Keywords: aversion learning; deleterious chemicals; polyphagy; preference; Spodoptera litura

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin